A phase II dose‑escalation trial of perioperative desmopressin (1‑desamino‑8‑D‑arginine vasopressin) in breast cancer patients - Weinberg, Ruth S. (2015)
Desmopressin (dDAVP) is a well-known peptide analog of the antidiuretic hormone vasopressin, used to prevent excessive bleeding during surgical procedures. dDAVP increases hemostatic mediators, such as the von Willebrand factor (vWF), recently considered a key element in resistance to metastasis. Studies in mouse models and veterinary trials in dogs with locally-advanced mammary tumors demonstrated that high doses of perioperative dDAVP inhibited lymph node and early blood-borne metastasis and significantly prolonged survival. We conducted a phase II dose-escalation trial in patients with breast cancer, administering a lyophilized formulation of dDAVP by intravenous infusion in saline, 30–60 min before and 24 h after surgical resection. Primary endpoints were safety and tolerability, as well as selection of the best dose for cancer surgery. Secondary endpoints included surgical bleeding, plasma levels of vWF, and circulating tumor cells (CTCs) as measured by quantitative PCR of cytokeratin-19 transcripts. Only 2 of a total of 20 patients experienced reversible adverse events, including hyponatremia (grade 4) and hypersensitivity reaction (grade 2). Reactions were adequately managed by slowing the infusion rate. A reduced intraoperative bleeding was noted with increasing doses of dDAVP. Treatment was associated with higher vWF plasma levels and a postoperative drop in CTC counts. At the highest dose level evaluated (2 μg/kg) dDAVP appeared safe when administered in two slow infusions of 1 μg/kg, before and after surgery. Clinical trials to establish the effectiveness of adjunctive perioperative dDAVP therapy are warranted. This trial is registered on www.clinicaltrials.gov (NCT01606072).